Rapid flow cytometry analysis of antimicrobial properties of hybrid arctic bramble (Rubus arcticus nothossp. x stellarcticus G. Larsson) and cloudberry (Rubus chamaemorus L.) - Jaakkola, Mari; Korhonen, Johanna; Hattuniemi, Maarit; Räty, Jarkko; Hoppula, Kalle; Virtanen, Vesa (cz, 2009)
v ok